A STUDY ON PATIENTS’ AWARENESS, RECOGNITION MANAGEMENT AND PREVALENCE OF HYPOGLYCEMIC EPISODES IN TYPE 2 DIABETES MELLITUS IN A TERTIARY CARE HOSPITAL - SOUJANYA AKKINENI; ANCY MARY MATHEWS; APUROOPA, GADEPALLI; SRIDHAR N, NEHA; PRUDENCE A RODRIGUES (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To assess patients' awareness on management of hypoglycemic episodes and analyzing the prevalence of hypoglycemic episodes in patients with Type 2 diabetes mellitus. Methods: A prospective-observational comparative study was carried out for a period of 6 months in the outpatient unit of endocrinology and general medicine department. Patients who had hypoglycemic episodes were classified into mild, moderate and severe hypoglycemia with respective to age, anti-diabetic therapy and co-morbidities. Prevalence of hypoglycemia was calculated using prevalence formula; hypoglycemic episodes for antidiabetic therapy were compared using ANOVA and independent t-test. Results: Of 200 patients, (43%) were male and (57%) were female patients. Patients with systemic hypertension (30%) were more predominant than other co-morbid conditions. According to anti-diabetic therapy (49.5%) patients were on oral hypoglycemic agents (OHA's), (16.5%) on insulin and (34.5%) on both insulin and OHA's. The calculated value of t (2.831) was greater than table value (2.45) and mean of OHA (24.75) was greater than the mean of insulin (8.25). Prevalence of hypoglycemia was (51%). Conclusion: The results from this study showed that more number of patients taking OHAs was found to experience hypoglycemia and patients with SHT as co-morbid condition were found to experience hypoglycemia than other co-morbid conditions. Prevalence of hypoglycemia was found to be more in females and elderly population. Keywords: Hypoglycemic episodes, Prevalence, Insulin, Oral hypoglycemic agents, Co-morbid condition.